Analysis of the Determinants of Implementing a Pharmacy Management Information System and its Impact on the Benefits of Pharmaceutical Services at Hospital X Bandung - Meti Siada; Maura Linda Sitanggang; Lies Putriana (SEAN Institute, 2023)
This research aims to analyze the influence of the determinants of implementing a pharmaceutical management information system on the benefits of pharmaceutical services at HOSPTAL X Bandung. This research uses a quantitative approach using a cross-sectional study design that measures many variables at one time. The sample in this study amounted to 223 samples. The research results show that almost all variables have an influence except that the Information Quality (KI) of the Pharmacy SIM and the Service Quality (KL) of the Pharmacy SIM do not have a significant effect on the benefits of pharmaceutical services; Pharmacy SIM variables do not have a significant effect on the benefits of pharmaceutical services through Pharmacy SIM user variables; Organizational variables do not have a significant effect on the benefits of pharmaceutical services through user satisfaction (KP) variables; and User Satisfaction (KP) does not have a significant effect on the benefits of pharmaceutical services.